1985
DOI: 10.1128/aem.49.5.1197-1205.1985
|View full text |Cite
|
Sign up to set email alerts
|

Effect of temperature, pH, and oxygen level on the multiplication of naturally occurring Legionella pneumophila in potable water

Abstract: A water culture containing naturally occurring Legionella pneumophila and associated microbiota was maintained in the laboratory by serially transferring the culture in tap water which had been sterilized by membrane filtration. Successful maintenance of the water culture depended upon transferring the culture when the growth of L. pneumophila was in the late-exponential to early-stationary phase. The water culture was used as a source of naturally occurring bacteria to determine some of the parameters which a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
86
1
1

Year Published

1988
1988
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 140 publications
(93 citation statements)
references
References 30 publications
5
86
1
1
Order By: Relevance
“…Legionella have never been detected in the same assays performed at 48°C, underlining that in our experimental conditions this temperature was too high for legionellae survival, as reported by other authors in experiments carried out in filter-sterilized waters [27,29,30]. Nonetheless, as legionella is detected in hot water systems [31], even at high temperatures, we must note that our artificial microcosms do not represent the real environment but give useful indications on the capability of Lp-1 to survive under definite and con-trolled experimental conditions.…”
Section: Resultssupporting
confidence: 79%
See 1 more Smart Citation
“…Legionella have never been detected in the same assays performed at 48°C, underlining that in our experimental conditions this temperature was too high for legionellae survival, as reported by other authors in experiments carried out in filter-sterilized waters [27,29,30]. Nonetheless, as legionella is detected in hot water systems [31], even at high temperatures, we must note that our artificial microcosms do not represent the real environment but give useful indications on the capability of Lp-1 to survive under definite and con-trolled experimental conditions.…”
Section: Resultssupporting
confidence: 79%
“…Lee and West [33] report that L. pneumophila suspended in sterilized tap or distilled water at 25°C, after initial fluctuations, may survive for long periods, up to 65 days, stabilizing at a level slightly above that initial concentration. Moreover, several groups, which performed the test by removing and replacing the microcosms with fresh sterile tap water at regular intervals, showed that L. pneumophila cultured at 35°C remained indefinitely without the addition of any nutrient other than those occurring naturally in the water [30,34].…”
Section: Discussionmentioning
confidence: 99%
“…up to 14 months in tap water with only a modest loss in culturability in the first few months (Skaliy and McEachern, 1979;Schofield, 1985). However, at high temperatures well above its ∼37°C growth optimal (Yee and Wadowsky, 1982;Wadowsky et al, 1985;Kusnetsov et al, 1996), the loss of culturability and viability in starved L. pneumophila is accelerated (Ohno et al, 2003). At 50°C, culturability dropped from 100% to 25% in 60 min (Groothuis and Veenendaal, 1983), and at >50°C, a clear loss of viability was observed after 40 min (Fliermans et al, 1981a).…”
Section: Introductionmentioning
confidence: 99%
“…These findings suggest that temperature around 30°C may be optimal for the multiplication of L. pneumophila. Wadowsky has indeed shown previously that multiplication of L. pneumophila occurred between temperatures of 25-37°C whereas at temperatures above 42"C, the actual number of L. pneumophila declined rapidly (Wadowsky et al, 1985a). Finally, the dissemination of legionella occurred only when the outlet water temperature was below 56°C.…”
Section: Discussionmentioning
confidence: 76%